Panax notoginseng WRKY Transcription Factor 9 Is a Positive Regulator in Responding to Root Rot Pathogen Fusarium solani - Zheng, Lilei; Qiu, Bingling; Su, Linlin; Wang, Hanlin; Cui, Xiuming; Ge, Feng; Liu, Diqiu (Frontiers in Plant Science, 2022)
Panax notoginseng (Burk) F.H. Chen is a rare and valuable Chinese herb, but root rot mainly caused by Fusarium solani severely affects the yield and quality of P. notoginseng herbal materials. In this study, we isolated 30 P. notoginseng WRKY transcription factors (TFs), which were divided into three groups (I, II, and III) on the basis of a phylogenetic analysis. The expression levels of 10 WRKY genes, including PnWRKY9, in P. notoginseng roots increased in response to a methyl jasmonate (MeJA) treatment and the following F. solani infection. Additionally, PnWRKY9 was functionally characterized. The PnWRKY9 protein was localized to the nucleus. The overexpression of PnWRKY9 in tobacco (Nicotiana tabacum) considerably increased the resistance to F. solani, whereas an RNAi-mediated decrease in the PnWRKY9 expression level in P. notoginseng leaves increased the susceptibility to F. solani. The RNA sequencing and hormone content analyses of PnWRKY9-overexpression tobacco revealed that PnWRKY9 and the jasmonic acid (JA) signaling pathway synergistically enhance disease resistance. The PnWRKY9 recombinant protein was observed to bind specifically to the W-box sequence in the promoter of a JA-responsive and F. solani resistance-related defensin gene (PnDEFL1). A yeast one-hybrid assay indicated that PnWRKY9 can activate the transcription of PnDEFL1. Furthermore, a co-expression assay in tobacco using β-glucuronidase (GUS) as a reporter further verified that PnWRKY9 positively regulates PnDEFL1 expression. Overall, in this study, we identified P. notoginseng WRKY TFs and demonstrated that PnWRKY9 positively affects plant defenses against the root rot pathogen. The data presented herein provide researchers with fundamental information regarding the regulatory mechanism mediating the coordinated activities of WRKY TFs and the JA signaling pathway in P. notoginseng responses to the root rot pathogen.